Huawei's Internationalization Strategy - Yang, Minxue; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
In the current strategic phase of Chinese enterprises "going global," they have received significant policy support, particularly in the high-end information technology industry, which is experiencing unprecedented growth. Huawei, as a leading company in the domestic communication market, has strategically positioned itself in the low-end market, steadily expanding its presence. It has also focused on technology absorption and has engaged in multiple collaborations with foreign companies while executing its internationalization strategy. As a result, Huawei has established a significant presence in international markets. This article delves into the internationalization strategy of Huawei, focusing on its operating environment and internal conditions. It also proposes policy recommendations and directions for further development.